Organic dust-induced lung injury and repair: Bi-directional regulation by TNFα and IL-10. Issue 1 (1st January 2020) - Wyatt, T. A.; Nemecek, M.; Chandra, D.; DeVasure, J. M.; Nelson, A. J.; Romberger, D. J.; Poole, J. A.
Abstract: Exposure to organic dust increases chronic airway inflammatory disorders. Effective treatment strategies are lacking. It has been reported that hog barn dust extracts (HDE) induce TNFα through protein kinase C (PKC) activation and that lung inflammation is enhanced in scavenger receptor A (SRA/CD204) knockout (KO) mice following HDE. Because interleukin (IL)-10 production can limit excessive inflammation, it was hypothesized here that HDE-induced IL-10 would require CD204 to effect inflammatory responses. C57BL/6 wild-type (WT), SRA KO, and IL-10 KO mice were intranasally challenged daily for 8 days with HDE and subsequently rested for 3 days with/without recombinant IL-10 (rIL-10) treatment. Primary peritoneal macrophages (PM) and murine alveolar macrophages (MH-S cells) were treated in vitro with HDE, SRA ligand (fucoidan), rIL-10, and/or PKC isoform inhibitors. HDE induced in vivo lung IL-10 in WT, but not SRA KO mice, and similar trends were demonstrated in isolated PM from same treated mice. Lung lymphocyte aggregates and neutrophils were elevated in in vivo HDE-treated SRA and IL-10 KO mice after a 3-d recovery, and treatment during recovery with rIL-10 abrogated these responses. In vitro rIL-10 treatment reduced HDE-stimulated TNFα release in MH-S and WT PM. In SRA KO macrophages, there was reduced IL-10 and PKC zeta (ζ) activity and increased TNFα following in vitro HDE stimulation. Similarly, blocking SRA (24 hr fucoidan pre-treatment) resulted in enhanced HDE-stimulated macrophage TNFα and decreased IL-10 and PKCζ activation. PKCζ inhibitors blocked HDE-stimulated IL-10, but not TNFα. Collectively, HDE stimulates IL-10 by an SRA- and PKCζ-dependent mechanism to regulate TNFα. Enhancing resolution of dust-mediated lung inflammation through targeting IL-10 and/or SRA may represent new approaches to therapeutic interventions.